Misaligned feeding schedule elicits divergent circadian reorganizations in endo- and exocrine pancreas clocks - Honzlová, Petra; Novosadová, Zuzana; Houdek, Pavel; Sládek, Martin; Sumová, Alena (Cellular and molecular life sciences, 2022)
Misaligned feeding may lead to pancreatic insufficiency, however, whether and how it affects circadian clock in the exocrine pancreas is not known. We exposed rats to a reversed restricted feeding regimen (rRF) for 10 or 20 days and analyzed locomotor activity, daily profiles of hormone levels (insulin, glucagon, and corticosterone) in plasma, and clock gene expression in the liver and endocrine and exocrine pancreas. In addition, we monitored responses of the exocrine pancreatic clock in organotypic explants of mPer2Luc mice in real time to acetylcholine, insulin, and glucocorticoids. rRF phase-reversed the clock in the endocrine pancreas, similar to the clock in the liver, but completely abolished clock gene rhythmicity and significantly downregulated the expression of Cpb1 and Cel in the exocrine pancreas. rRF desynchronized the rhythms of plasma insulin and corticosterone. Daily profiles of their receptor expression differed in the two parts of the pancreas and responded differently to rRF. Additionally, the pancreatic exocrine clock responded differently to treatments with insulin and the glucocorticoid analog dexamethasone in vitro. Mathematical simulation confirmed that the long-term misalignment between these two hormonal signals, as occurred under rRF, may lead to dampening of the exocrine pancreatic clock. In summary, our data suggest that misaligned meals impair the clock in the exocrine part of the pancreas by uncoupling insulin and corticosterone rhythms. These findings suggest a new mechanism by which adverse dietary habits, often associated with shift work in humans, may impair the clock in the exocrine pancreas and potentially contribute to exocrine pancreatic insufficiency.
Keywords: Circadian Clocks; Insulin; inzulin; pankreas exokrinní; Corticosterone; Misaligned feeding; Dexamethasone; Pancreas; cirkadiánní rytmus; Glucocorticoids; Circadian Rhythm; Pancreas, Exocrine; krysa rodu Rattus; Animals; kortikosteron; glukokortikoidy; zvířata; Rats; myši; mPer2Luc mouse; Circadian clock; Mice; cirkadiánní hodiny